2016
DOI: 10.1002/cmdc.201500600
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ketobenzothiazole Serine Protease Inhibitors of Aberrant HGF/c‐MET and MSP/RON Kinase Pathway Signaling in Cancer

Abstract: Upregulation of the HGF and MSP growth-factor processing serine endopeptidases HGFA, matriptase and hepsin is correlated with increased metastasis in multiple tumor types driven by c-MET or RON kinase signaling. We rationally designed P1' α-ketobenzothiazole mechanism-based inhibitors of these proteases. Structure-activity studies are presented, which resulted in the identification of potent inhibitors with differential selectivity. The tetrapeptide inhibitors span the P1-P1' substrate cleavage site via a P1' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…Both the MET kinase inhibitor JNJ38877605 and SRI 31215 inhibit signaling between cancer cells and HGF-producing fibroblasts, blocking fibroblast-induced proliferation, EMT and migration of cancer cells. We confirmed that structurally distinct triplex inhibitors of matriptase, hepsin and HGFA block the crosstalk between tumor cells and fibroblasts [ 66 ]. Furthermore, we demonstrated that SRI 31215 overcomes fibroblast-mediated resistance to EGFR inhibitors in colon cancer cells.…”
Section: Discussionsupporting
confidence: 63%
“…Both the MET kinase inhibitor JNJ38877605 and SRI 31215 inhibit signaling between cancer cells and HGF-producing fibroblasts, blocking fibroblast-induced proliferation, EMT and migration of cancer cells. We confirmed that structurally distinct triplex inhibitors of matriptase, hepsin and HGFA block the crosstalk between tumor cells and fibroblasts [ 66 ]. Furthermore, we demonstrated that SRI 31215 overcomes fibroblast-mediated resistance to EGFR inhibitors in colon cancer cells.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, structural analysis of the complexes of KD1 and HGF/SF‐activating proteases may have significant implications for the development of synthetic chemicals that specifically inhibit proteolytic activation of HGF/SF and MSP. To date, several promising small molecular weight compounds that specifically inhibit the HGF/SF‐activating proteases have been reported . Generation of neutralizing antibodies against these proteases may also be a useful approach.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In urological cancers, several small molecule inhibitors targeting MET have been used in PC and RCC in clinical trials, and cavozantinib is used as a major agent targeting MET and VEGFR in patients with advanced RCC [90,91,108,109]. In addition, the efficacy of several agents for HGF and the activating TTSPs, including anti-HGF antibody, antibodies and small molecule inhibitors of hepsin and matriptase, has been reported [3,40,[110][111][112][113]. Unfortunately, however, no such specific inhibitors have been verified in clinical trials [3,10].…”
Section: Discussionmentioning
confidence: 99%